Planning a global knowledge city: experience from Melbourne, Australia. (2019) - Tuli, Sajeda C.; Hu, Richard; Dare, Lain
This study investigates planning policy shifts to shape a global knowledge city in the dual contemporary transformative processes of globalisation and the knowledge economy. It develops an integrative conceptual and policy analytical framework from cross-fertilising 'the global city' and 'the knowledge city', and tests it by applying it to Melbourne as a case study. The empirical analysis involves a content analysis of strategic plans and elite interviews with key policy makers and informants. The findings are mixed. At both the state and the city levels, the strategic plans demonstrate a growing presence and importance of key themes that define Melbourne as an emerging global knowledge city. However, the absence of a national policy and problematic inter-governmental coordination in strategic directions, and a lack of focus on human capital without due considerations of home grown talent and international students, are limiting Melbourne from fully reaching its potential as a global knowledge city. Drawing on these findings, this study concludes with a discussion about the effectiveness of the constructed framework in conceptualising 'the global knowledge city' and policy analysis; it also points out a few limitations of this exploratory study that require further research.